Developing Lifelong Singers Through Exploration, Performance, and Reflection: Supplemental File 1 - Boller, Sean (My University, 2019)
In my videos you will see three different lessons and two different grade levels. In lesson one, sixth grade students are learning about musical form and preparing to use Sound Trap to create an original composition in rondo form. Lesson two, my high school women’s choir rehearsed and prepared for their state contest. The last video shows the women’s choir discussing the Kansas State High School Activities Association State rubric and explaining what each category is and what they think it means. After the rubric was explained they listened to themselves perform, rated themselves and justified their ratings. Kansas State University has exposed me to many teaching strategies and has helped me grow as an educator. The two major developments in my teaching have been the use of assessments in the classroom, whether it is peer assessment or self-assessment, and the approach I take to teaching new music. I have learned that I do not need to spoon feed my students new music. The moment that I relinquished control and allowed them to explore and make mistakes I began to see a higher level of accountability from them. My students have learned to be more independent by me stepping back and allowing them to grow as musicians and humans.
Keywords: Creating music; Performing Music; Responding to Music